2014
DOI: 10.1136/injuryprev-2013-041005
|View full text |Cite
|
Sign up to set email alerts
|

Informing policy on open water drowning prevention: an observational survey of life jacket use in Washington state

Abstract: Highest life jacket use was strongly associated with laws requiring use and with adult role modelling. Legislation requiring life jackets for ages 13-17 years and social marketing encouraging adult life jacket wear in the company of children and youth are promising strategies to increase life jacket use in Washington State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 10 publications
3
43
0
Order By: Relevance
“…This figure is consistent with estimations reported from observational studies of PFD use by boaters conducted in 2007 in the four Australian states without comprehensive mandatory PFD wearing regulations (range 8–28%),15 Canada (20%),16 and the three Washington state and regional studies (17–21% for motor boaters) 4 6 8. The US 2012 national life jacket wear rate observational study reported that wearing rates among adults on powerboats was consistently low between 1999 and 2012 (range 3.9% to 5.2%) 7.…”
Section: Discussionsupporting
confidence: 88%
“…This figure is consistent with estimations reported from observational studies of PFD use by boaters conducted in 2007 in the four Australian states without comprehensive mandatory PFD wearing regulations (range 8–28%),15 Canada (20%),16 and the three Washington state and regional studies (17–21% for motor boaters) 4 6 8. The US 2012 national life jacket wear rate observational study reported that wearing rates among adults on powerboats was consistently low between 1999 and 2012 (range 3.9% to 5.2%) 7.…”
Section: Discussionsupporting
confidence: 88%
“…One study, using population-based data from the Australian state of Victoria, found that compulsory life jacket wear regulations did not cause a significant reduction in fatal drowning among those aged 60+, as it had in other age groups 52. Conversely, a second study reported adult life jacket use was lowest among those aged 65 years and older 54. A third, using observational studies, found a 56% increase life jacket wear among those aged 60+ in small power vessels as a result of legislation 53…”
Section: Resultsmentioning
confidence: 99%
“…The US Coast Guard reports that in 2012 PFD usage in the USA was 22.6% among all boaters, 67.5% among youth under 18 and 9.3% among adults ages 18 and above 12. A 2010 observational study of boats in Washington State reported that PFD usage rates were 30.7% among all boaters and 22–18% among those over the age of 12 13. In Washington State, children ages 12 and under are required to wear a USCG-approved PFD at all times when underway in a boat less than 19 ft in length, unless in a fully enclosed area 14.…”
Section: Discussionmentioning
confidence: 99%